Las políticas sociales luego de 2001 y hasta 2015:«Resolviendo» la paradoja entre la «segmentación» y la «inclusión» - Brown, Brenda (Universidad Nacional del Litoral, 2021)
From the critical theory, this article studies the Argentine social policy from 2001 to 2015. This analysis is carried out in light of the aspects assumed by the labor market during this period, which are characterized by be of economic growth with a total employment increase, but also due to the persistence of some employment problems that are consolidated and presented as structural and difficult to reverse. In this framework and, In this framework and, using content analysis as a methodological tool, in this article it is maintained that the State, through social policies, parado xically reproduce the segmentation of the labor market since, on the one hand, identifying this problem is difficult to reverse —implementing specific policies for the specifically vulnerable population— on the other, promoting the blurring of the borders between the employed population and the unemployed population and between the different segments of workers that make up the labor market.